Longer growing seasons will not offset growth loss in drought-prone temperate forests of Central-Southeast Europe - Tumajer, Jan; Kašpar, Jakub; Altman, Jan; Altmanová, Nela; Camarero, J Julio; Cienciala, Emil; Čada, Vojtěch; Čihák, Tomáš; Doležal, Jiří; Fibich, Pavel; Janda, Pavel; Kaczka, Ryszard; et al. (Nature communications, 2025)
The radial growth of temperate forests responds to climate change with remarkable variation across space and between species. However, there is limited understanding of how growing season extension and increasing drought stress contribute to long-term growth trends. Here, we calibrate the VS-Lite growth model using 2013 tree-ring chronologies from ten broadleaved and five coniferous genera in Central-Southeast Europe to predict intra-annual wood formation under four SSP climate scenarios through the 21st century. Results show that forecasted summer drought stress will be temporarily offset by an extended growing season, leading to stable or positive trends in tree-ring widths until a tipping point in the 2040s-2050s. During the second half of the 21st century, high-emission scenarios lead to growth acceleration in humid coniferous forests due to growing season extension and enhanced growth rate. In contrast, forecasted extension of the growing season is insufficient to compensate for declining summer growth rates at drier sites, resulting in significant growth reduction for all genera, particularly during dry years. Our results demonstrate that adjusting intra-annual wood formation to seasonal moisture availability may become crucial for tree survival in warmer climates. Furthermore, we highlight that only low-emission scenarios support non-declining stem growth in dry forests with current species composition.
Keywords: Droughts; Seasons; klimatické změny; Evropa; dřevo; roční období; lesy; Europe; stromy; Forests; Trees; Climate Change; období sucha; Wood